Despite NAIS concerns electronic identification use by cow-calf producers is increasing - Breiner, S.J.; Grau, S.A.; Barnhardt, B.B.; Bryant, A.M.; Boone, Kris; Blasi, Dale A.; Schroeder, Ted C.; Breiner, Ryan M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The proposed U.S. National Animal Identification System has generated concerns among producers relative to implementation of the system. Many of these concerns stem from the USDA’s Bovine Identification Working Group’s recommendations to use electronic Identification Plan Bovine Working Group has recommended radio frequency identification as the technology to individually identify cattle. Understanding and implementing an electronic identification system for cow-calf producers is believed to be one of the greatest challenges of implementing the National Animal Identification System.
Keywords: Beef; Cattle; National Animal Identification (NAIS); The U.S. Animal Identification Plan Bovine Working Group